Mangrove Plantation Program in the Lenses of Bajau in Kaledupa Island, Wakatobi Regency: Community Perceptions - Setyaningrum, Arista; Fasa, La; Ariando, Wengki (GMPI Conference Series, 2022)
The restoration of the coastal areas through mangrove plantations has become an appropriate practice to substantiate sustainable resources management. Community involvement and targeted program implementation are the main factors affecting social welfare and environmental security. Labour Intensive Mangrove Planting (PKPM) is a program initiated by the Ministry of Environment and Forestry of the Republic of Indonesia as a national economic recovery during the Covid-19 pandemic. Kaledupa Island, Wakatobi Regency, Southeast Sulawesi is one area that was replanted mangroves about 81 hectares. As implemented, this program works with some communities such as Bajau Sampela and Mantigola. This research aimed to investigate the community perceptions of socio-cultural changes of the Bajau community in Kaledupa in the short term from the PKPM program. A qualitative approach with an ethnographic method was applied to this study and in-depth interview (n=6) to Wakatobi National Park (WNP) authority from September 2020 to June 2021. Bajau is having a strong relationship with nature in an ecological complexity system. The perception of the Bajau community to PKPM was based on short-term economic motives. Various existence issues as follows community participation and leadership, co-management system, customary conflicts in coastal area management, and strengthening traditional ecological knowledge are the points of discussion in this study. Bajau communities are presuming the degradation of their cultural identity and governance system that is very vulnerable to adopting the disruptive era without proper knowledge and dependency on nature. Involvement of customary institutions in sustainable mangrove management of Bajau in Kaledupa island should acknowledge the transdisciplinary integration and shareholders participation. Nevertheless, PKPM briefly helps in giving back the trust issue of Bajau communities to WNP authority and accelerates community-based conservation bridging to sustainable development goals from local practices.